Analisis Kesiapan Implementasi Rekam Medis Elektronik Ditinjau Dari Sumber Daya Manusia DI RSU Anwar Medika Sidoarjo - Mudzakir, Abdul Kohar (ARTERI : Jurnal Ilmu Kesehatan, 2024)
The use of Electronic Medical Record by hospitals is important. As the basic regulations in article 3 of Minister of Health Regulation No. 82 of 2013 concerning SIMRS require Electronic Medical Record to be implemented in each hospital. Electronic Medical Records or abbreviated as EMR to create an optimal and excellent service system. The purpose of this research is to analyze hospital readiness in implementing RME in terms of Human Resources at RSU Anwar Medika Sidoarjo. This research is qualitative-descriptive research, to obtain results the researcher used an empirical approach. The research location is located at RSU Anwar Medika, Sidoarjo, East Java Province in 2024. The research results show that the use of Electronic Medical Record is understood by employees as a replacement for manual medical records in digital form, this is to simplify, speed up, optimize excellent service and reduce paper use. So that the RSU's human resources can be seen from the operation of the EMR system starting from the first health service (queuing, registration, giving examination numbers and codes) to internal services (diagnostic records, medical consultations, giving prescriptions) carried out by RSU Anwar Medika based on the RME system. So that, the existing human resources are included in the category of being able to carry out processing of "documents containing patient identity data, examinations, treatment, actions" with an RME-based health service system.